2019
DOI: 10.1182/blood-2019-129421
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bridging Chemotherapy on Clinical Outcomes of CD19 CAR T Therapy in Relapse/Refractory Diffuse Large B- Cell Lymphoma in Real World Experience

Abstract: Background: Autologous chimeric antigen receptor (CAR) T cell therapy has shown to be effective in relapsed or refractory (R/R) diffuse large B cell lymphoma (DLBCL) but requires in real world and in Europe at least a 4 weeks period of cell processing. During this "bridging period", patients are vulnerable to disease progression and complications. We sought to characterize bridging therapy strategies. Methods: We performed a retrospective review of patients (pts) with R/R DLBCL treated with comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Until now, there is no standard bridging therapy, and a preferred strategy has yet to be identified. 37 To avoid using additional chemotherapies that would further impair patients' already taxed immune systems, clinicians are considering other strategies, such as the use of radiotherapy or biological therapy. Radio therapy in particular seems to be a safe and effective…”
Section: Treatment-related Factorsmentioning
confidence: 99%
“…Until now, there is no standard bridging therapy, and a preferred strategy has yet to be identified. 37 To avoid using additional chemotherapies that would further impair patients' already taxed immune systems, clinicians are considering other strategies, such as the use of radiotherapy or biological therapy. Radio therapy in particular seems to be a safe and effective…”
Section: Treatment-related Factorsmentioning
confidence: 99%
“…This raises concern about the identification of optimal bridging therapy for these patients, as these strategies were not allowed in the ZUMA-1 trial and are typically needed in patients with high-risk disease ( 55 ). Unfortunately, real-world data show a heterogeneous pattern of the use of bridging therapies, and a preferred strategy has yet to be identified ( 56 , 57 ). Of interest, recent data demonstrated that radiation therapy may be a safe and effective bridging approach; in particular, it may limit myelosuppression and favorably impact the host immune tumor microenvironment ( 58 60 ).…”
Section: Axi-cel For Aggressive B-cell Lymphomamentioning
confidence: 99%
“…Two retrospective studies have also evaluated the use of bridging therapy. The first evaluated 46 patients who were receiving commercial CAR T products and included 30 (65%) who received high‐intensity bridging therapy, defined as chemotherapy with or without immunotherapy, and 16 (35%) who received low intensity or no bridging therapy [ 25 ]. In this study, the intensity of bridging treatment was closely related to tumor burden at enrollment and while there was no difference in efficacy of CAR T infusion between the high‐intensity and low‐intensity groups, similar to other studies the high‐intensity group did have a higher frequency of CRS and neurotoxicity.…”
Section: Previous Experience With Bridging Therapymentioning
confidence: 99%